Writing into the Future : New American Poetries from the Dial to the Digital. - Golding, Alan (Modern and Contemporary Poetics Ser., 2022)
"A career-spanning collection of essays from a leading scholar of avant-garde poetry, this work collects Alan Golding's essays on the futures (past and present) of poetry and poetics. Throughout the 13 essays gathered in this collection, Golding skillfully joins literary critique with a concern for history and a sociological inquiry into the creation of poetry. In Golding's view, these are not disparate or even entirely distinct critical tasks. He is able to fruitfully interrogate canons and traditions, both on the page and in the politics of text, culture, and institution. A central thread running through the chapters is a longstanding interest in how various versions of the "new" have been constructed, received, extended, recycled, resisted, and reanimated in American poetry since modernism. To chart the new, Golding contends with both the production and the reception of poetry, in addition to analyzing the poems themselves. In a generally chronological order, Golding reconsiders the meaning for contemporary poets of high modernists like Ezra Pound and William Carlos Williams, as well as the influential poetry venues The Dial and The Little Review, where less prominent but still vital poets contested what should come "next." Subsequent essays track that contestation through The New American Poetry and later anthologies. Mid-century major figures like Robert Creeley and George Oppen are discussed in their shared concern for the serial poem. Golding's essays bring us all the way back to the present of the poetic future, with writing on active poets like Rachel Blau DuPlessis, Susan Howe, and Bruce Andrews and on the anticipation of digital poetics in the material texts of Language writing. Golding charts the work of defining poetry's future and how we rewrite the past for an unfolding present"--